APLICAÇÃO E AVALIAÇÃO DAS TECNOLOGIAS COMO FERRAMENTAS DE APOIO EDUCACIONAL NA ODONTOLOGIA - COSTA, Maria Aparecida (2016)
Applications or existing software are currently in continuous process of evolution and transformation and are widely used by people with different proposals and purposes (communication, entertainment, management, education, health, etc.). Given this scenario, new teaching methods and tools to support education have been developed in the teaching-learning process. Thus, this study aims to explore the educational tools based on information technologies. For this, an integrative review of the literature on applications used in oral health from 2005 to 2015 (Chapter I) was held initially, noting that little research has explored these tools aimed at the prevention of mouth diseases and the promotion of oral health for the professional training; there is a lot of work with applications aimed at children, and support for graduation. Most studies with applications in oral health focused on orthodontics area and general practice. Therefore, it is noted in the context of primary care, a gap to be exploited through the use of information technology. Thus, in Chapter II, it was proposed the development and validation of a serious game that consists of a questions and answers scheme addressing children and teenager’s oral health content, directed to dental professionals.